Forestry and economic growth in Ghana: evaluating the dynamics using the environmental Kuznets curve and adjusted net savings - Joseph Antwi Baafi; Kwame Acheampong; Michael Kwame Asiedu; Pearl Seyram Kumah (Forestry Economics Review)
Purpose – This study investigates the link between economic growth, environmental sustainability and deforestation in Ghana, aiming to identify the economic drivers of deforestation and assess how sustainable economic practices can mitigate its rates. Design/methodology/approach – The study used secondary data from 1980 to 2023. It applied quantitative techniques, including regression, vector error correction model and multiple Granger causality to examine the impact of GDP growth, adjusted net savings (ANS) and other control variables on Ghana’s deforestation rate. Findings – The analysis supports environmental Kuznets curve (EKC) hypothesis, indicating that deforestation initially rises with GDP but declines at higher levels. It finds a long-term relationship where economic growth correlates with reduced deforestation. ANS promotes sustainable growth, while FDI increases deforestation. Research limitations/implications – The study supports the EKC hypothesis, indicating that economic growth initially increases deforestation but that ANS positively impacts long-term GDP growth. It emphasizes directing FDI toward sustainable sectors to mitigate deforestation. Overall, integrating environmental sustainability into economic planning is crucial for Ghana’s growth. Practical implications – To support sustainable economic development in Ghana, policies should integrate environmental sustainability into growth strategies and standardize adjusted net savings as a metric for evaluating resource-intensive projects. Directing FDI toward sustainable industries, along with stabilizing inflation, can help mitigate deforestation while promoting eco-friendly practices. Originality/value – This study’s originality lies in analyzing Ghana’s forestry and economic growth through the EKC framework and adjusted net savings from 1980 to 2023. Unlike prior research, this paper addresses overlooked interactions between growth, environmental sustainability, population growth and FDI using more recent, stable data relevant to current policy decisions.